Effects of Music Training on Inhibitory Control and Associated Neural Networks in School-Aged Children: A Longitudinal Study - Hennessy, Sarah L.; Sachs, Matthew E.; Ilari, Beatriz; Habibi, Assal (Frontiers in Neuroscience, 2019)
Inhibitory control, the ability to suppress an immediate dominant response, has been shown to predict academic and career success, socioemotional wellbeing, wealth, and physical health. Learning to play a musical instrument engages various sensorimotor processes and draws on cognitive capacities including inhibition and task switching. While music training has been shown to benefit cognitive and language skills, its impact on inhibitory control remains inconclusive. As part of an ongoing 5-year longitudinal study, we investigated the effects of music training on the development of inhibitory control and its neural underpinnings with a population of children (starting at age 6) from underserved communities. Children involved in music were compared with children involved in sports and children not involved in any systematic after-school program. Inhibition was measured using a delayed gratification, flanker, and Color-Word Stroop task, which was performed both inside and outside of an MRI scanner. We established that there were no pre-existing differences in cognitive capacities among the groups at the onset. In the delayed gratification task, beginning after three years of training, children with music training chose a larger, delayed reward in place of a smaller, immediate reward compared to the control group. In the flanker task, children in the music group, significantly improved their accuracy after three and four years of training, whereas such improvement in the sport and control group did not reach significance. There were no differences among the groups on behavioral measures of Color-Word Stroop task at any time point. As for differences in brain function, we have previously reported that after two years, children with music training showed significantly greater bilateral activation in the pre-SMA/SMA, ACC, IFG, and insula during the Color-Word Stroop task compared to the control group, but not compared to the sports group (Sachs et al., 2017). However, after four years, we report here that differences in brain activity related to the Color-Word Stroop task between musicians and the other groups is only observed in the right IFG. The results suggest that systematic extracurricular programs, particularly music-based training, may accelerate development of inhibitory control and related brain networks earlier in childhood.